Comparison of anthropometric measures as predictors of cancer incidence: A pooled collaborative analysis of 11 Australian cohorts. Issue 7 (6th April 2015) - Harding, Jessica L.; Shaw, Jonathan E.; Anstey, Kaarin J.; Adams, Robert; Balkau, Beverley; Brennan‐Olsen, Sharon L.; Briffa, Tom; Davis, Timothy M.E.; Davis, Wendy A.; Dobson, Annette; Flicker, Leon; Giles, Graham; et al.
<x xml:space="preserve">Abstract</x> Obesity is a risk factor for cancer. However, it is not known if general adiposity, as measured by body mass index (BMI) or central adiposity [e.g., waist circumference (WC)] have stronger associations with cancer, or which anthropometric measure best predicts cancer risk. We included 79, 458 men and women from the Australian and New Zealand Diabetes and Cancer Collaboration with complete data on anthropometry [BMI, WC, Hip Circumference (HC), WHR, waist to height ratio (WtHR), A Body Shape Index (ABSI)], linked to the Australian Cancer Database. Cox proportional hazards models assessed the association between each anthropometric marker, per standard deviation and the risk of overall, colorectal, post‐menopausal (PM) breast, prostate and obesity‐related cancers. We assessed the discriminative ability of models using Harrell's c‐statistic. All anthropometric markers were associated with overall, colorectal and obesity‐related cancers. BMI, WC and HC were associated with PM breast cancer and no significant associations were seen for prostate cancer. Strongest associations were observed for WC across all outcomes, excluding PM breast cancer for which HC was strongest. WC had greater discrimination compared to BMI for overall and colorectal cancer in men and women with c‐statistics ranging from 0.70 to 0.71. We show all anthropometric measures are associated with the overall, colorectal, PM breast and obesity‐related cancer in men and women, but not prostate cancer. WC discriminated marginally better than BMI. However, all anthropometric measures were similarly moderately predictive of cancer risk. We do not recommend one anthropometric marker over another for assessing an individuals' risk of cancer.